2014
DOI: 10.1136/jech-2014-204091
|View full text |Cite
|
Sign up to set email alerts
|

Fetal ultrasound measurements and associations with postnatal outcomes in infancy and childhood: a systematic review of an emerging literature

Abstract: BackgroundSeveral hypotheses predict that faltering fetal growth is an antecedent for common non-communicable diseases. This is the first systematic review of an emerging literature linking antenatal fetal measurements to postnatal outcomes.MethodsElectronic databases (OVID, EMBASE and Google Scholar) and cohort study websites were searched in July 2014. Studies were selected which examined associations between antenatal fetal ultrasound measurements and postnatal outcomes. Neonatal outcomes, e.g. premature de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 48 publications
1
35
0
Order By: Relevance
“…Our findings confirm previously described association between change in abdominal circumference between the second and third trimesters and altered eczema risk and atopy risk , but the novel finding is that the direction of the relationship is reversed in the Saudi population compared with populations in the Netherlands and UK. A recent systematic review has identified apparently inconsistent findings between antenatal growth and postnatal outcomes between different populations ; for example, blood pressure has been positively and negatively associated with femur length, and the results presented here compliment the findings of the systematic review and support the principle of predictive adaptive responses or developmental plasticity where a fetus might reach more than one postnatal phenotype depending on the antenatal cues experienced at critical points of development.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Our findings confirm previously described association between change in abdominal circumference between the second and third trimesters and altered eczema risk and atopy risk , but the novel finding is that the direction of the relationship is reversed in the Saudi population compared with populations in the Netherlands and UK. A recent systematic review has identified apparently inconsistent findings between antenatal growth and postnatal outcomes between different populations ; for example, blood pressure has been positively and negatively associated with femur length, and the results presented here compliment the findings of the systematic review and support the principle of predictive adaptive responses or developmental plasticity where a fetus might reach more than one postnatal phenotype depending on the antenatal cues experienced at critical points of development.…”
Section: Discussionsupporting
confidence: 72%
“…Importantly, the observations to date linking antenatal fetal growth to outcomes, such as eczema risk, are limited to populations in Australia, the Netherlands, the USA, and UK where the antenatal environment and potential confounders are similar. Studies in non‐Western populations, where antenatal environmental cues may differ, may give new understanding of the developmental origins of disease .…”
mentioning
confidence: 99%
“…Up to one-third of SGA infants are not FGR but are simply constitutionally small,16 and while identification of FGR infants is improved by the use of birthweight centiles, their use alone will still include many normal infants 17. These difficulties have led to inconsistent findings, with some studies showing a modest or negligible effect of SGA on cognitive outcome when standard centiles alone are used 18. Improved postnatal assessment of risk would help clinicians and parents to target follow-up and early intervention.…”
Section: Introductionmentioning
confidence: 99%
“…too big or small) when there is a mismatch between antenatal cues and the postnatal environment. A small number of groups have established cohorts to test the DOHaD by measuring antenatal and postnatal growth and relating this to NCDs, which in children are limited to asthma and relatively few other conditions …”
mentioning
confidence: 99%
“…A small number of groups have established cohorts to test the DOHaD by measuring antenatal and postnatal growth and relating this to NCDs, which in children are limited to asthma and relatively few other conditions. 6 The exact relationship between very early (antenatal) growth and respiratory outcomes in childhood is not clear from the small number of publications currently available, but a study in this issue of Respirology brings some clarity. 7 The work by Sonnenschein-van der Voort et al 7 reports associations between antenatal and postnatal growth, asthma symptoms and pulmonary function at 6 years of age.…”
mentioning
confidence: 99%